Bee-diverse habitats positively affect seed set in wild plant species - Heuel, Kim C.; Ayasse, Manfred; Burger, Hannah (Frontiers in Ecology and Evolution, 2024)
Interactions between flowering plants and visiting wild bees are crucial for ensuring pollination and subsequent plant reproductive success. However, bee diversity in an area has rarely been recorded in relation to seed set in native plants. In this project, we performed pollination experiments to investigate the effect of local wild bee communities on seed set in four common wild plant species, namely Centaurea jacea, Cichorium intybus, Sinapis arvensis, and Salvia pratensis (all in pots), in two distinct habitat types that we expected to show distinct bee communities, namely near-natural grassland and perennial wild flower strips, in Germany. Our results showed that near-natural grassland had a higher bee species richness and an increased seed set compared with flower strips that displayed a higher bee abundance in most study locations. Although we found effects of bee diversity on seed set, we did not detect a significant effect of bee abundance. Furthermore, the seed set in response to wild bee diversity differed across the plant species. We conclude that bee-friendly habitats ensure a high seed set in wild plants, but that the impact varies between different plant species.